ANALISIS PENGARUH INDIKATOR BRAND RESONANCE TERHADAP BRAND LOYALTY PADA PENGGUNA SEPEDA LISTRIK DI SOLO RAYA - Okta Bella Fatin; Moechammad Nasir (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the effect of Brand Resonance indicators on Brand Loyalty in electric bicycle users in Solo Raya. This research method uses a quantitative approach. The data collection method in this study uses a quantitative approach. The population in this study were all residents of Greater Solo who owned electric bicycles. Sampling technique with non-probability sampling using purposive sampling approach. Sampling refers to the Ferdinan formula. The number of samples in this study were 250 respondents. This research uses primary data. The data collection method in this study uses Google forms. The data analysis method in this study uses Partial Least Square (PLS). The results of this study are Brand credibility does not have a significant influence on Brand Loyalty for Electric Bicycle users in Solo Raya. Service quality does not have a significant influence on Brand Loyalty for Electric Bicycle users in Solo Raya. Customer Satisfaction has a significant influence on Brand Loyalty for Electric Bicycle users in Solo Raya. Brand awareness has a significant influence on Brand Loyalty for Electric Bicycle users in Solo Raya. Based on the calculation, the coefficient of determination (R²) shows that the variables of brand credibility, service quality, customer satisfaction and brand awareness have a large contribution to brand loyalty.